Effects of GnRH or hCG on day 11 after artificial insemination in cows luteal activity - Besbaci, Mohamed Mohamed; Abdelli, A.; Belabdi, I.; Benabdelaziz, A; Khelili, R.; Mebarki, M.; Kaidi, R. (Journal of the Hellenic Veterinary Medical Society, 2019)
In order to optimize luteal function by human chorionic gonadotrophin (hCG) or gonadotrophin releasing hormone (GnRH) on day 11 after artificial insemination (AI). 33 cows synchronized by the Ovsynch and divided into 3 groups according to the type of treatment: 1) hCG (1500 IU, n=11); 2) GnRH (100 µg, n=11); and 3) control (2 mL of saline, n=11). Blood samples were collected from all animals every 3 days from day 5 to day 23 to determine progesterone concentration. Ultrasonography was used to monitor the luteal surface structures at the time of blood sample collection. An accessory corpus luteum (CL) formed in 63.63% of cows treated with GnRH and with hCG, resulting in an increase in the total luteal tissue area compared with the controls. Thus, the volume of the principal CL was increased by hCG but tended to be similar to GnRH compared with the controls. Additionally, compared with the control group, hCG-treated and GnRH-treated cows had increased progesterone concentrations (p<0.0001). Among the hCG-treated cows, their progesterone concentration increased compared with GnRH-treated cows.